2019
DOI: 10.7759/cureus.5952
|View full text |Cite
|
Sign up to set email alerts
|

Does Google™ Have the Answers? The Internet-based Information on Pelvic and Acetabular Fractures

Abstract: IntroductionThe aim of this study is to assess the readability and reliability of internet-based information on pelvic and acetabular fractures.MethodsThe three most popular English-based internet search engines are Google, Yahoo, and Bing. Quality was assessed using the DISCERN tool, the Journal of the American Medical Association tool, and the presence of the Health on the Net Code (HONcode) seal. Readability was assessed using a combination of the Flesch Reading Ease Score and the Flesch-Kincaid grade level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“… 6 Recent studies assessing content on orthopaedic trauma found information to be poor (between 29% and 47% of maximum quality scores). 10 11 12 13 This study found HON scores ranging from 42% to 73% of maximum scores, and between 21% and 50% of websites were deemed high-quality based on HON score. This suggests that websites on fragility fracture and osteoporosis are of similar or slightly better quality compared with other orthopaedic websites.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“… 6 Recent studies assessing content on orthopaedic trauma found information to be poor (between 29% and 47% of maximum quality scores). 10 11 12 13 This study found HON scores ranging from 42% to 73% of maximum scores, and between 21% and 50% of websites were deemed high-quality based on HON score. This suggests that websites on fragility fracture and osteoporosis are of similar or slightly better quality compared with other orthopaedic websites.…”
Section: Discussionmentioning
confidence: 65%
“… 7 9 No studies have assessed information content on fragility fractures specifically; however, some recent studies have investigated orthopaedic trauma, including clavicle fractures, scaphoid fractures, distal radius fractures, and pelvic/acetabulum fractures and found information to be poor. 10 11 12 13 The literature on content of osteoporosis websites was mostly published before 2010. These findings are likely outdated, given the rapid change in Internet content but consistently found information to be of inadequate quality.…”
mentioning
confidence: 99%
“…Numerous studies reveal that the content quality of information for laypersons on health on websites is mostly poor. 9,10 Quality-based studies of YouTube content for information concerning dentistry (ie, orthodontics, botulinum toxin for bruxism, impacted canines, dental implants, etc) have been performed. 7,[11][12][13] Literature reviews reveal that quality and accuracy of information on Artificial Intelligence in Dental Radiology (AIDR) have yet to be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies reveal that the content quality of information for laypersons on health on websites is mostly poor 9,10 . Quality‐based studies of YouTube content for information concerning dentistry (ie, orthodontics, botulinum toxin for bruxism, impacted canines, dental implants, etc) have been performed 7,11‐13 .…”
Section: Introductionmentioning
confidence: 99%
“…Medical information is no exception, and the term “consulting Dr. Google” has been popularized to represent searching for medical information on the internet [ 1 ]. Various studies have investigated the reliability and accuracy of medical information acquired on the internet [ 2 - 4 ]. However, there has been no research to specifically examine the extent to which medical information from websites supervised by medical associations is acquired from search results.…”
Section: Introductionmentioning
confidence: 99%